2011
DOI: 10.1016/j.rpor.2011.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of lung cancer in the elderly: Influence of comorbidity on toxicity and survival

Abstract: Our results allow us to conclude that elderly patients are likely to benefit from radical treatments. Chemo-radiotherapy seems to increase survival but should be used carefully in old patients outside clinical trials. Comorbidities did not seem to influence survival and toxicity of treatments, although larger studies are necessary to prove this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
1
8
1
Order By: Relevance
“…Comorbid diseases and functional impairment are clearly associated with a poorer prognosis. 5 Similarly, problems with mental, emotional, or nutritional status, polypharmacy, and lack of family or social support can interfere with the effectiveness and tolerability of treatment, with negative implications for outcome and survival. 6 Patient assessment is more subjective than tumor assessment, but no less important.…”
Section: Patient Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid diseases and functional impairment are clearly associated with a poorer prognosis. 5 Similarly, problems with mental, emotional, or nutritional status, polypharmacy, and lack of family or social support can interfere with the effectiveness and tolerability of treatment, with negative implications for outcome and survival. 6 Patient assessment is more subjective than tumor assessment, but no less important.…”
Section: Patient Factorsmentioning
confidence: 99%
“…A study from Kaiser Permanente of Northern California sought to establish adherence by examining prescription refill data on 8769 patients with breast cancer who filled prescriptions for tamoxifen only (43%), AI only (29%), or both (30%) within 1 year of a diagnosis of breast cancer. 5 Patients were considered to be "adherent" if the number of pills dispensed in prescriptions from the date of the first prescription to the end of follow-up covered at least 80% of the days in the entire period. This statistic is called the medication possession ratio (MPR).…”
Section: Treatment Compliancementioning
confidence: 99%
“…Results of conventional external beam radiation for early stage NSCLC are disappointing, 5 with local relapse as the predominant pattern of failure leading to different 5-year survival rates according to primary tumour dimensions: 38% for patients with tumours < 2 cm, 22% for tumours between 2 and 3 cm, 5% for tumours between 3 and 4 cm and 0% for larger lesions. 6 In order to improve tumour control and, hence, cancer-specific survival (CSS), dose-escalation gained credit as an option, but when considering the dose-response relationship for lung cancer, doses up to 80-90 Gy would be needed to control approximately 50% of the tumours.…”
Section: Sabr Vs Conventional Radiotherapy In Inoperable Patientsmentioning
confidence: 99%
“…it has been demonstrated that hypertension can lead to the intensification of side effects of taking trastuzumab and anthracyclines, in the form of cardiomyopathy. [16][17][18] Comorbidities lead to polypharmacy. Many medicines interact with cytostatics or other agents used in oncological treatment, bringing the risk of unexpected and potentially serious adverse effects.…”
Section: What Does Cga Consist Of?mentioning
confidence: 99%